REKAYASA ASPEK KENYAMANAN PEDESTRIAN KAWASAN JALAN DI PANDJAITAN SEBAGAI RUANG TERBUKA PUBLIK UNTUK MENDUKUNG âLIVABLE STREET - , LEMBAH TRI LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A road becomes a liaison between the centers of urban activity that reflects the life and vitality of the city. Therefore planning of a road becomes very important when you want to develop an area. A road that is comfortable, safe, attractive and can accommodate the needs of all users, it will increase the life of the road area. As is the case in the study area is located in DI Pandjaitan road, that is a comfortable road but less interesting that not many visitors who utilize the site. This causes the region to be fairly quiet and less lively. Though actually the road has the potential to be developed, considering the strategic location, close to some fairly well-known tourist attractions in Yogyakarta. Therefore, needed a planning to engineer the potential of road, to be used as a capital of in the area of road to enliven DI Pandjaitan road. Comfort and vitality will be the main factor that will be analyzed in this planning study. It also used the concept of Livable Street approach as a basis for planning guidelines. Considering the Livable Street is a planning concept, where a road that can accommodate the needs of all road users, including pedestrians, cyclists, motorists, parents, adults, children, and the diffable. With the creation of a Livable Street in the DI Pandjaitan road, the area is expected in the future will be a living area and has a friendly roads, convenient, and safe for all road users.